Membrane guanylate cyclase, a multimodal transduction machine: history, present, and future directions - Sharma, Rameshwar K.; Duda, Teresa (Frontiers in Molecular Neuroscience, 2014)
A sequel to these authors’ earlier comprehensive reviews which covered the field of mammalian membrane guanylate cyclase (MGC) from its origin to the year 2010, this article contains 13 parts. The first is HISTORICAL and covers MGC from the year 1963-1987, summarizing its colorful developmental stages from its passionate pursuit to its consolidation. The second deals with the establishment of its BIOCHEMICAL IDENTITY. MGC becomes the transducer of a hormonal signal and founder of the peptide hormone receptor family, and creates the notion that hormone signal transduction is its sole physiological function. The third defines its EXPANSION. The discovery of ROS-GC subfamily is made and it links ROS-GC with the physiology of PHOTOTRANSDUCTION. Parts 4 to 7 cover its BIOCHEMISTRY and PHYSIOLOGY. The noteworthy events are that augmented by GCAPs, ROS-GC proves to be a transducer of the free Ca2+ signals generated within neurons; ROS-GC becomes a two-component transduction system and establishes itself as a source of cyclic GMP, the second messenger of phototransduction. Part 8 demonstrates how this knowledge begins to be TRANSLATED into the diagnosis and providing the molecular definition of retinal dystrophies. Part 9 discusses a striking property of ROS-GC where it becomes a “[Ca2+]i bimodal switch” and transcends its signaling role in other neural transduction processes. In this course, discovery of the first CD-GCAP (Ca2+-dependent guanylate cycles activator), the S100B protein, is made. It extends the role of ROS-GC transduction system beyond the photoreceptor cells to the signaling processes in the synapse region between photoreceptor and cone ON-bipolar cells; in Part 10, discovery of ANOTHER CD-GCAP, NC, is made and its linkage with signaling of the inner plexiform layer neurons is established. Part 11 discusses linkage of the ROS-GC transduction system with other sensory transduction processes: Pineal gland, Olfaction and Gustation. In the next, part 12, a theo